Effects of People-oriented Leadership and Subordinate Employability on Call Center Withdrawal Behaviors - Federico R. León; Oswaldo Morales (Journal of Work and Organizational Psychology, 2018)

(untitled)
Call-center employees are prone to lateness, absenteeism, and turnover because their jobs are low-wage, low-skill, and provoke high levels of stress. Thus, considerate supervisors achieve from them better performance and reduced turnover. This study tested in a Peruvian call center (N = 255) various hypotheses concerned with the effects of people-oriented leadership on withdrawal behaviors, their moderation by subordinate perceived employability, and the nature of the relationships between withdrawal behaviors. The evidence revealed independence of uncertified absenteeism from turnover intention, negative effects of people-oriented leadership on subordinate turnover intention regardless of subordinate level of employability, and leadership x employability crossover interactive effects on subordinate uncertified absenteeism. Since people-oriented supervision is associated with increased absenteeism among highly employable subordinates and decreased absenteeism among low-employability workers, the effects cancel each other. Thus, there is a need for understanding the underlying determinants as a pre-condition to deriving practical recommendations.